“Valoración de neutrófilos segmentados en bovinos de la ganadería FACIAG-UTB tratados con hemoautotransfucion” - Barona Rodriguez, Dennisse Desiree (2023)
In the present experimental work was carried out in the Faculty of Agricultural Sciences of the Technical University of Babahoyo in the Livestock area, the assessment of segmented neutrophils was carried out in bovines treated with hemoautotransfusion. For the test, 10 bovines divided into two groups of five were used, obtaining from additional evidence a witness for each group, for which the treatments were of two types of 15ml and 20ml of autologous blood. 2 types of treatments with 6 repetitions were used giving 12 experimental units with 6 animals per Experimental Unit, therefore a Completely Random Design (DCA) was used, the Tukey mean comparison method was also used at 5% of numerical significance. The results were subjected to analysis of variance in the Infostat/L statistical program. When obtaining the results of each week, it was possible to verify the data through the analysis of variance and the mean. In week 1, after 24 hours of hemoautotransfusion, we obtained the result that the control (0ml) achieved an excellent response in its mean of 3.55 uL, while that of 15 ml was 2.37 uL and that of 20ml reached a value of 2.53 uL. In week 2 (7 days) of having made hemoautotransfusion, a variation was verified in the series of segmented neutrophils in the 0 ml dose as a result of its average of 3.96 uL. In week 3 (14 days) in the 0ml dose, a higher average of 3.36 uL was reached. At week 4 (21 days) there was an alteration with the 0ml dose with a corresponding mean of 3.66 uL. In week 5 (28 days) at the end of the hemoautotransfusion treatment with doses of 15ml and 20ml, the most relevant dose was 0ml with a mean of 3.67 uL. When comparing each procedure with ruminants, it was achieved that there was no variation in the series of neutrophils in healthy cattle, this means that hemoautotransfusion is not recommended in healthy cattle and is required to be applied to sick animals.